Analysis of Health Belief Model in Adolescent Groups of Drug Users - Wahyuningtyas, Ramadhani; Amanda, Qurry; Desriani, Ririn; Firman, Firman; Alard, Van Houten; Fadly, Ahmad (Universitas Ahmad Dahlan, 2024)
Background: The use of drugs (narcotics, psychotropics, and addictive substances) among adolescents in urban areas is increasing and is a concern for the benefit of public health, especially in an effort to maintain a healthy generation. This study aims to identify the health belief model in adolescent groups of drug users. Methods: This qualitative study employed a phenomenological design. The research focused on an unassisted drug user in Yogyakarta, who was not under the care of the National Narcotics Agency (NNA). Data was gathered through a Focus Group Discussion (FGD) involving six informants. Triangulation of information sources included the NNA and Drug Non-Governmental Organizations (NGOs). Data analysis was conducted using content analysis. Result: This study reveals that adolescents who use drugs tend to rely on self-treatment when seeking health services. They base their approach on assessing the symptoms and manageable effects of opium drugs, either individually or in groups. Their initial step involves consuming specific foods or beverages believed to counteract the drug's effects. This practice is influenced by advice from peers and information obtained from the Internet. Additionally, their reluctance to utilize healthcare facilities is reinforced by a fear of legal consequences. Conclusion: The health belief model in adolescent drug user groups in Yogyakarta is self-treatment. Thus, collaborative socialization and education efforts are needed between stakeholders (NNA, NGOs, Healthcare Facilities, and Schools). They should focus on enhancing awareness about the available health service programs for drug users, their types, and how to access them.